Research Note: Association of temporal expression of myostatin with hypertrophic muscle growth in different Japanese quail lines - Kim, Dong-Hwan (Poult Sci, 2020)
Myostatin (MSTN) negatively regulates in muscle growth and development. Among alternative splicing isoforms of avian MSTN, MSTN-A has antimyogenic activities and MSTN-B functions as a promyogenic factor. In this study, different lines of Japanese quail were used: a random bred control (RBC) and a heavy weight (HW) quail line with muscle hypertrophy. The objectives of the current study are to compare temporal expression of the MSTN isoforms in pectoralis major muscle (PM) between 2 quail lines and to relate MSTN expression with temporal changes in muscle growth and total amounts of DNA in PM. Gains of body weight (BW) and PM weight were greater until posthatch day (D) 28 (P < 0.001), and the fold increases in total DNA contents of PM were greater in the HW line compared with the RBC line during D7 to D28 (P < 0.05). PCR analysis showed that MSTN-A expression was greater at 14 D (E14) of embryonic age (P < 0.01), D7 (P = 0.052), and D14 (P < 0.01) in the RBC line compared with the HW line. At D28 and D75, expression of MSTN-A was greater in the HW line compared with the RBC line (P < 0.05). MSTN-B expression was barely detectable from E14 to D14 and measurable from D28 to D75 in the muscle of both lines. Ratios of the MSTN-B/-A form ranging from 0.15 to 0.29 indicate a minor expression of the B form. Taken together, the lesser expression levels of MSTN-A at E14, D7, and D14 are associated with the fast growth of PM, and greater MSTN-A expression at D28 and D75 are associated with a slowdown of PM growth in the HW line. These data indicate a negative association of MSTN expression with PM growth and provide a scientific basis for potential usage of MSTN expression as a selection marker for greater muscle growth in poultry.